Reinterpretasi Kata dan Rasa Ilmu Psikolinguistik: Strategi Membangun Ketahanan Mental bagi Generasi Muda - Agus Try Any Marpaung; Indah Thyansika Manihuruk; Monica Monalisa Hutabarat; M. Surip (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Today’s young generation faces a variety of complex challenges, such as academic pressure, social media dynamics, and high social expectations, which can trigger stress, anxiety, and burnout. Burnout, characterized by emotional exhaustion, decreased motivation, and feelings of helplessness, is increasingly experienced by the younger generation. Mental resilience, or the ability to bounce back from adversity and adapt to change, is key in facing these challenges. This study explores the role of psycholinguistics, the study of the relationship between language, thought, and behavior, in building the mental resilience of the younger generation. Through a qualitative approach and literature review, this study identifies psycholinguistic-based strategies, such as the use of positive words, reframing, and therapeutic storytelling, to improve mental resilience. The results show that positive and constructive language can help the younger generation manage stress, increase self-confidence, and build a more resilient mindset.